Pengaruh Keterlibatan dan Pengetahuan Produk Terhadap Keputusan Pembelian Jamu Masuk Angin Kemasan - Intan Tri Annisa; Angga Pandu Wijaya (Management Insight: Jurnal Ilmiah Manajemen, 2019)
This purpose study is examines the effect of product knowledge and product involvement toward purchase decision on herbal medicine catches a cold packaging. This study was conducted based on quantitative approach. Data collected using online survey and involved 121 respondents. Data analysis was employed using ANOVA. The results of this study revealed that the effect of product knowledge significant positively toward purchase decision on herbal medicine catches a cold packaging. The effect of product involvement significant positively toward purchase decision on herbal medicine catches a cold packaging so.